(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Punarnava (Boerhavia diffusa Linn.) is a traditional medicinal herb. It is widely distributed in India as well as worldwide. This plant has wide biodiversity with 40 species. It is found in tropical, sub-tropical and temperate regions of the World. It has a great share in the AYUSH trading. Several herbal companies and pharma units are consuming a lot of quantity of Boerhavia crude drugs. The herbal market is dominated by Boerhavia and some many other Indian herbal products, even crude drug markets are also playing a major role in the Indian economy like Khari Bavli in Delhi, Herbal center in Dehradun, Trade Center in Bhopal and Raipur, etc. Many pharma companies are manufacturing a huge number of products that are used by people for different ailments. About 15 essential amino acids are found in the plant. Potassium nitrate and Punarnavine alkaloid are found in plenty of amount. Punarnava is used in the kidney, liver, spleen, and neural diseases. NMPB and allied agencies are trying to uplift the trade in herbal drugs in the world so that we could be able to stand first in the world.